Zebrafish; an emerging model organism for studying toxicity and biocompatibility of dental materials - Karaman, Gözde Ece; Emekli-Alturfan, Ebru; Akyüz, Serap (Cellular and Molecular Biology, 2020)
Zebrafish (danio rerio) is a small, tropical freshwater teleost fish that belongs to the Cyprinidae family and lives in natural waters and rice fields in South Asia, North India, and Pakistan. Zebrafish has become a popular vertebrate model organism for biomedical research due to its numerous advantages such as their small size, short life cycle, accessibility in large numbers and inexpensive maintenance. In addition, fertilization happens externally in zebrafish and allows zebrafish to be manipulated directly. As another important advantage, the embryos are transparent thus the stages of development can be easily identified. Zebrafish can have multiple co-orthologs for human genes. In the 1930s, the zebrafish was first used as a model for developmental and embryological studies and in 1981, was introduced as a genetic model by Streisinger by force of developed genetic techniques in zebrafish such as cloning, mutagenesis and transgenesis. In the 1990s, various genetic manipulations were introduced. These improvements have contributed to the popularity of zebrafish. After that zebrafish was used in various research areas including genetics, biomedicine, neurobiology, toxicology, pharmacology as well as in human disease models. Zebrafish is also becoming a popular model organism in dental research. It is preferred in dental material toxicity studies and in research related to the genetic and molecular factors in tooth formation and craniofacial development. This review provides information on the use of zebrafish in dental research, focusing on tooth formation and dentition (pharyngeal dentition) of zebrafish and the dental research performed using zebrafish.